Extraordinary fast-twitch fiber abundance in elite weightlifters - Serrano, N.; Colenso-Semple. L. M.; Lazauskus, K. K.; Siu, J. W.; Bagley, J. R.; Lockie, R. G.; Costa, P. B.; Galpin, A. J. (PLOS ONE, 2018)
Human skeletal muscle fibers exist across a continuum of slow ? fast-twitch. The amount of each fiber type (FT) influences muscle performance but remains largely unexplored in elite athletes, particularly from strength/power sports. To address this nescience, vastus lateralis (VL) biopsies were performed on World/Olympic (female, n = 6, "WCF") and National-caliber (female, n = 9, "NCF"; and male, n = 6, "NCM") American weightlifters. Participant accolades included 3 Olympic Games, 19 World Championships, 25 National records, and >170 National/International medals. Samples were analyzed for myosin heavy chain (MHC) content via SDS-PAGE using two distinct techniques: single fiber (SF) distribution (%) and homogenate (HG) composition. The main finding was that these athletes displayed the highest pure MHC IIa concentrations ever reported in healthy VL (23±9% I, 5±3% I/IIa, 67±13% IIa, and 6±10% IIa/IIx), with WCF expressing a notable 71±17% (NCF = 67±8%, NCM = 63±16%). No pure MHC IIx were found with SF. Secondary analysis revealed the heavyweights accounted for 91% of the MHC IIa/IIx fibers, which caused a correlation between this FT and body mass. Additionally, when compared to SF, HG overestimated MHC I (23±9 vs. 31±9%) and IIx (0±0 vs. 3±6%) by misclassifying I/IIa fibers as I and IIa/IIx fibers as IIx, highlighting the limitation of HG as a measure of isoform distribution. These results collectively suggest that athlete caliber (World vs. National) and/or years competing in the sport determine FT% more than sex, particularly for MHC IIa. The extreme fast-twitch myofiber abundance likely explains how elite weightlifters generate high forces in rapid time-frames.